Properties of choroid and ciliary neurons in the avian ciliary ganglion and evidence for substance P as a neurotransmitter - Dryer, SE (J Neurosci, 1985)
Intracellular recordings were made from identified choroid and ciliary neurons in the ciliary ganglion of the embryonic chick. Choroid neurons, which were innervated by multiple preganglionic fibers, frequently displayed noncholinergic slow excitatory postsynaptic potentials (EPSPs) following repetitive stimulation of the preganglionic nerve trunk. These slow potentials were blocked by high Mg2+/low Ca2+ buffer and were closely mimicked by bath application of substance P, which is known to be present within both populations of preganglionic nerve terminals. Substance P-induced depolarizations desensitized during prolonged exposure, at which time it was no longer possible to evoke slow synaptic potentials. Following manual voltage clamp to resting membrane potential, parallel increases in input resistance were seen during the slow EPSP and the response to substance P, suggesting that the two responses share common mechanisms. Ciliary neurons, which were innervated by a single preganglionic fiber and displayed dual electrical-chemical synapses, did not exhibit slow synaptic potentials and were unaffected by bath application of substance P. The magnitude and time course of fast nicotinic EPSPs elicited in ciliary neurons by 0.5 Hz presynaptic stimulation were also unchanged in the presence of 1 to 3 microM substance P. Although the ciliary and choroid neurons share a common embryological origin in the neural crest, they are specialized for quite different physiological roles. Integration of multiple presynaptic inputs occurs at choroid synapses, mediated by the presence of both subthreshold fast nicotinic EPSPs and the slow EPSP. In contrast, synapses on ciliary neurons have specializations which preclude any integrative function, including single innervation, a high quantal content, electrical coupling potentials, and a lack of slow synaptic potentials.